The Effectiveness of Implementing Collaborative Online Learning Between Professions In A Pandemic Period - Nurhaeni, Heni; Astit Karmawati, Ita; Yulita, Ita; Tarwoto; Tyastuti, Dwi (International Journal of Social Service and Research, 2021)
Interprofessional Collaboration (IPE/C) is a form of developing health services for all health workers. In the Jakarta I Poltekkes environment since 2018, IPE/C-based learning has been developed to provide opportunities for nursing, midwifery, orthotic prosthetics and dental students to have direct experience in collaborating between professions (IPE/C) in public health services. Implementation of collaborative practice models in acute, primary, and community care. However, over time IPE/C activities were able to improve the quality of health services by using 4 domains; Roles, Communication, Norms/Values, Ethics, and Inter-Professional Communication. Courses with a â€œpeople-centered careâ€ approach have strategies/methods: Demonstration, roleplay, discussion, and PBC, Tutorial, PBD/Independent, online media (zoom) and Library Studies on the documentation system. And during the Pandemic period, learning is carried out through online media with a maximum meeting time of 90 minutes and alternate breaks to anticipate device malfunctions with the link provided from Pusbangdik, namely Join Zoom Meetings. During 2 weeks of online learning, the students' achievements were obtained with an average score of 87.06, an increase of 56.7%, and 98% of students/lecturers stated that they were very satisfied with the joint learning.